EKSPERIMENTAL KINERJA SISTIM REFRIGERASI AIR CONDITIONER SPLIT TERHADAP PARAMETER PENGUJIAN DENGAN KOMBINASI PEMANFAATAN DAN PEMASANGAN WATER HEATER LISTRIK - Martin Luther King; Iskandar Husin; Hermanto . (Universitas Tridinanti Palembang, 2018)
Frequent complaints from workers in the company regarding the unavailability of hot water for bathing water needs during the rainy season. To fulfill hot water needs for company workers, it is necessary to install a water heater in each mess for comfort for workers. This experiment is also in line with supporting the Government and Company programs in terms of the efficiency of the energy and global warming beneficiaries that are currently happening. Water heater technology (WH) is considered the most recent and used as an alternative. Its main function is to supply hot water needs in all parts of the housing that are in need. The amount of heated water is adjusted to the needs of the dwelling whether it's for bathing, kitchen matters, and washing. Because it is used when needed, the efficiency side is greatly highlighted from the water heater product (WH). Another advantage of the product concerned is the unlimited supply of hot water provided there is always electricity available Key Words: Air Conditioner, Water Heater, Heat, Energy Efficiency